Call variability, stereotypy and relationships in syntopy of tetraploid common lesser escuerzo (Anura: Genus Odontophrynus) - Grenat, Pablo Raúl (2017)
We studied patterns of the geographic variation of mating calls of the common lesser escuerzo Odontophrynus americanus including populations living in syntopy with the closely related O. cordobae and adjacent allopatric populations. The dominant frequency, pulse rate, call duration and pulses/call showed the lowest intra-individual variation (CV < 3%). The discriminant function analysis (DFA) assigned 88% of all calls to the correct individual, indicating that the advertisement calls of O. americanus are individually distinctive. Call duration, pulses per call and the dominant frequency were likely related to individual distinctiveness. Pulse rate and pulse temporal parameters related consistently showed the lowest values of CV b /CV w ratio and could be considered key properties for species recognition in O. americanus. We found a greater call divergence between species in syntopy than in allopatry in terms of the pulse rate and particularly the interpulse interval. These results appear to be consistent with a pattern of reproductive character displacement. Further studies testing female selectivity should be essential to evaluate whether acoustic differences observed between syntopic and allopatric populations are biologically significant and if there are differences in selectivity between such areas.